Evaluasi Implementasi Blended Learning dengan Pendekatan Theory Plan Behavior - Idram, Arief Harkat (Syntax Idea, 2021)
Blended Learning can also be a word with Hybrid Learning, similar to the name of a learning method that combines face-to-face learning with online learning. and also an integration between traditional classroom methods and online activities or e-learning. This method can maximize the transfer rate of funds where to know which one is from where by face-to-face by face-to-face online. However, the implementation of this method is constrained by the habits or habits of teaching a life span that has been cultivated so as to change it out of its habit is a careful planning. The Planned Behavior Theory or Plan Behavior Theory (TPB) explains that, human action is created by three kinds: beliefs about the results of behavior and results of these results (behavioral beliefs), about the normative expectations of others and for the motivation of expectations (normative beliefs), beliefs there will be factors that can be processed or performance performance of behavior and strength factors In combination, Attitude to Behavior, subjective norms, and perceptions of Behavioral Control turn into behavioral intentions. In general rules, the more attitudes / attitudes and subjective norms (subjective norms), and the greater perceived control / control felt, the stronger the intention to conduct behaviors that have a strong intention behavior. At the time, while his control over the bermusying, people hoped to be wronged their intentions there was a chance.